Identification of optimized rod shapes to guide anatomical spinal reconstruction for adolescent thoracic idiopathic scoliosis. Issue 12 (22nd August 2018) - Kokabu, Terufumi; Kanai, Satoshi; Abe, Yuichiro; Iwasaki, Norimasa; Sudo, Hideki
ABSTRACT: Adolescent idiopathic scoliosis (AIS), the most common pediatric musculoskeletal disorder, causes a three‐dimensional deformity of the spine. Although rod curvature could play an important role in anatomical spinal reconstruction in patients with thoracic AIS, intraoperative contouring of the straight rod induces notches into the rod, leading to decreased fatigue strength. Here, we analyzed pre‐bent rod geometries from 46 intraoperative tracings of the rod geometry, which can provide anatomical spinal reconstruction in patients with thoracic AIS. The center point clouds of the rod shapes were extracted and approximated as arcs and straight lines. The difference between the center point clouds were evaluated using the iterative closest point methods. When the rod shapes were divided into six groups based on length followed by hierarchical cluster analysis, 10 representative rod shapes were obtained with a difference value of 5 mm. Thus, we identified optimized rod shapes to guide anatomical spinal reconstruction for thoracic AIS, which will reduce not only the risk of rod breakage but also operation time, leading to decreased patient burden. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:3219–3224, 2018.